Arduino Uno Based Audiometer Design - Mohamad Sofie; Muhammad Rizky Aditya Firdaus; Bayu Wahyudi (Lembaga Pengembangan Kinerja Dosen, 2025)
The ability to detect hearing impairment early is an important aspect of preventive efforts in the field of ear and hearing health. An audiometer is a device used to measure a person's hearing threshold by presenting sound stimuli at various frequencies and intensities. This research aims to design and build a simple digital audiometer that can be used as a means of early hearing screening at primary healthcare facilities. The developed audiometer system uses a microcontroller as the control center, equipped with a user interface based on an LCD screen and buttons for adjusting frequency and sound intensity. Sound output is channeled through headphones and calibrated within the frequency range of 125 Hz to 10,000 Hz with intensity levels from 0 dB to 10 - 100 dB. The value obtained from the measurements after making improvements on TP 1 (Input adapter) showed an error of 0.03% TP 2 (Nextion LCD input) at 5.12 V which is still within tolerance. TP 3 (Arduino Input) at 11.64 V which is still within tolerance. TP 4 (Input IC LM2956) at 11.66 V which is still within tolerance. The function of this audiometer tool was tested using a digital multimeter. The highest error value is at a frequency of 500 Hz, which is 0.152%. This is partly due to the tolerance values of the components used. Based on the data collection using a sound level meter, the furthest difference in sound intensity values at the point of 40 dB was found to be 3.46 dB. This is due to the influence of noise in the surrounding measurement area.